The response to the Covid19 pandemic and the state of the autonomies - Lasagabaster Herrarte, Iñaki (EUNOMÍA. Revista en Cultura de la Legalidad, 2020)
The State's response to the pandemic caused by Covid19 has been carried out by declaring the state of alarm. The author considers that going to the state of alarm has placed politics in the key of command –military– when transparency and self-responsibility of citizens should have been the guiding principles. Health regulations are sufficient to respond to the pandemic, and aspects related to interterritorial mobility in need of state regulations, which could only be covered by the declaration of the state of alarm for that purpose. The CCAA are competent in matters of health, education, commercial activity, as well as public order, especially those that have their own police. For this reason, the competent authorities delegated should have been autonomous and not state. The joint action should have been developed through instruments of coordination and not by directly assuming the powers. The regional and / or local response to the situation would have been adequate due to its flexibility and adaptation to the circumstances. The de-escalation has shown this. The State has acted as if the regional governments did not exist, mainly at the beginning of the pandemic.
Keywords: Covid19 pandemic; state of alarm; autonomous competences